A Study on Recognizing the Value of Chestnut (Castanea sativa) Blossom Waste - Ümit Serdar; Aslı Özkök; Halil İbrahim Güler; Zehra Can; Yakup Kara; Sevgi Kolaylı; Hüseyin Şahin (Journal of Agricultural Sciences)
Chestnut (Castanea sativa) blossoms are natural resources that are not put to economic use. They are completely mixed with soil as waste. Thus, this extensive study was designed and remarkable results were found showing the potential usefulness of chestnut blossoms. In addition to the phenolic capacity and antioxidant capacity of the aqueous and ethanolic extracts of dried chestnut flowers, the anti-urease activity of these extracts was studied to demonstrate their therapeutic value. The binding interaction of phenolic substances present in chestnut blossom with urease was shown using molecular docking research. The aqueous extract, with most effect, had total phenolic content of 46.67 ± 0.37 mg GAE/g and total flavonoid content of 6.14 ± 0.40 mg QUE/g. The antioxidant activity was determined by FRAP (648.47 ± 5.27 μmol FeSO4.7H2O/g for aqueous extract and 347.53 ± 2.09 μmol FeSO4.7H2O/g for ethanolic extract) and DPPH (0.05 ± 0.01 mg/mL for SC50 of aqueous extract and 0.11 ± 0.01 mg/mL for SC50 of ethanolic extract) assays, and rutin was found to be the dominant phenolic compound according to HPLC. IC50 values for urease in aqueous and ethanolic extracts were 2.55 ± 0.09 mg/mL and 4.57 ± 0.24 mg/mL, respectively. According to the docking experiments, which were important to support the hypothesis of anti-urease activity, myricetin and luteolin showed different and effective bonding degrees to the target protein when compared with the reference molecule acetohydroxamic acid. In summary, chestnut flowers are rich in phenolic compounds which are responsible for a wide range of biological activities including antioxidant features and urease inhibition. These blossoms could be evaluated as potentially important raw materials for food.